Factors influencing spike jump height in female college volleyball players - Ikeda, Y.; Sasaki, Y.; Hamano, R. (The Journal of Strength and Conditioning Research, 2018)
The purpose of this study was to examine factors influencing spike jump (SPJ) performance by female competitive volleyball players through comparisons of the kinematic data of SPJ with those of the standing long jump (SLJ) and vertical jump (VJ). Seventeen female competitive volleyball players were asked to perform SPJ, SLJ, and VJ. Motion data of SPJ including the approach phase were recorded. Regarding SLJ and VJ, jumping motion and ground reaction force were recorded during each performance. The results obtained showed that SPJ height correlated with vertical velocity at take-off, horizontal velocity at third step contact, and the deceleration of horizontal velocity from third step contact to take-off. Regarding the relationship among SPJ, SLJ, and VJ, the relationship between SPJ and SLJ was stronger than that with VJ. The contributions of the hip, knee, and ankle muscles to the propulsive phase of SLJ were 39.7%, 21.1%, and 39.2%, respectively, whereas their contributions to VJ were 36.2%, 30.2%, and 33.6%, respectively. The vertical velocity of SPJ at take-off correlated with hip work and ankle peak power in SLJ and knee peak power in VJ. These results suggest the importance of enhancing horizontal and vertical jumping abilities separately to improve the height of SPJ because the primary generator for power production seems to depend on jump direction.